Evaluation of the rapid phase change absorbents based on potassium glycinate for CO2 capture. (5th June 2023) - Cao, Yongda; Yang, Chenglong; Wang, Chao; Zhou, Changan; Song, Lei; Ma, Kui; Lu, Houfang; Yue, Hairong
Graphical abstract: Highlights: The phase behavior of GlyK-H2 O-SA systems with different ratios was investigated. 2 M GlyK-30SA absorbent behaves the liquid–liquid phase separation within 2 min. 2 M GlyK-30SA system achieved over 91% CO2 enrichment with a loading of 0.64 mol/mol. 2 M GlyK-30SA system has a 30% reduction in energy consumption compared to MEA. The mechanism of the split phase and regeneration was explored by 13 C NMR. Abstract: Phase-change process is deemed as an energy-saving approach for CO2 capture, however, the low phase change rate of the current absorbents leads to low separation efficiency, difficult operation and solvent loss. Herein, a novel rapid phase change absorbent composed of ether solvent (SA) and potassium glycinate (GlyK) aqueous solution was developed, and the phase-change behavior, phase separation mechanism, and the energy consumption were investigated. Results showed that the GlyK-30SA absorbent exhibited the highest CO2 capacity of 0.64 molCO 2 /molGlyK, the liquid-liquid phase separation within 2 min and more than 91% CO2 enrichment in the lower phase. The mechanism of the split phase and regeneration was explored by 13 C NMR. More significantly, the absorbent also showed excellent cycling stability and a 30% reduction in energy consumption compared to the 3 M MEA system. It provided a new possibility for the development of stable and energy-saving amino acid salts phase change absorbents.